GBS operators of bivariate Bernstein‐Durrmeyer–type on a triangle. (14th February 2018) - Ruchi, Ruchi; Baxhaku, Behar; Agrawal, Purshottam N.
Abstract : The purpose of the present paper is to define the GBS (Generalized Boolean Sum) operators associated with the two‐dimensional Bernstein‐Durrmeyer operators introduced by Zhou 1992 and study its approximation properties. Furthermore, we show the convergence and comparison of convergence with the GBS of the Bernstein‐Kantorovich operators proposed by Deshwal et al 2017 by numerical examples and illustrations.